The use of reading aloud activity to improve pronunciation by using narrative text - Maryani, Dita; Seinsiani, Izzati Gemi (ELT Forum: Journal of English Language Teaching, 2025)
This study aimed to investigate the implementation of reading aloud activities using narrative texts to improve students’ pronunciation at a public elementary school in Semarang. Many elementary students faced challenges in pronouncing English accurately, largely due to a lack of awareness of phonetic elements, a limited vocabulary, and anxiety about making errors. Addressing these issues early was considered essential to avoid long-term communication problems and loss of self-confidence. This study employed a qualitative method to examine how reading aloud activities were implemented and to explore students’ perspectives on their role in improving pronunciation. Data were gathered through classroom observations, interviews with both students and the English teacher, and an analysis of reading sessions. The results indicated that incorporating narrative texts into reading aloud activities significantly improved students’ pronunciation by enhancing their awareness of phonetic features. Additionally, students expressed that these activities boosted their confidence, motivation to speak English, and active class participation. Nonetheless, obstacles such as limited vocabulary and the fear of making mistakes remained challenges that required further attention. The study concluded that reading aloud using narrative texts was a valuable strategy in teaching pronunciation, and it recommended integrating explicit phonetic instruction and vocabulary teaching to optimize learning outcomes. This research contributed to the improvement of English language teaching practices in elementary schools by emphasizing interactive and contextually relevant oral activities, such as reading aloud narrative texts, which can significantly improve students’ pronunciation and foster speaking confidence.